THE ORIGIN OF THE CONCEPT OF GASTRONOMIC TOURISM AND ITS HISTORICAL BASIS (Scientific journal of the Fergana State University, 2023)
The main purpose of this article is to shed light on the origin and essence of gastronomic tourism, as gastronomic tourism is now recognized as the main type of tourism in many developed countries, as the rapid development of gastronomic tourism is an important factor in economic growth. Therefore, it is important to conduct research on the theoretical, methodological and practical aspects of the development of gastronomic tourism.In this research work abstract-logical analysis, systematic analysis, comparative analysis have been used.Аfter reviewing the historical roots of gastronomic tourism, as well as the current scientific and practical processes in foreign countries and Uzbekistan, the need for the development of gastronomic tourism and the promotion of gastronomic tourism in this regard. It was concluded that it is necessary to promote initiatives, increase the level of knowledge in this area in our country, involve local authorities, public organizations, the media in this area, develop long-term planned training and working programs, further expand international cooperation.